Aeromodelling sebagai Bentuk Pembinaan Olahraga Dirgantara di SMA Muhammadiyah 1 Karanganyar Jawa Tengah - Santoso, Prasidananto Nur; Kurniawan, Freddy; Zabidi, Yasrin; Hartini, Dwi; Suhanto, Suhanto; Suyoko, Suyoko (Pakis Journal Institute, 2025)
Exercise has become an essential necessity as its benefits in one's physical development have been widely recognized. In addition, regular exercise also makes a positive contribution to mental health by reducing stres levels. Aeromodelling is a type of educational exercise that can reduce stres. Even so, interest in the aerospace sport is still low due to a lack of understanding of its benefits. Through aeromodelling training, especially among students, participants are introduced to the basic concepts of flight. In addition to training creativity, these activities can improve participants' analytical skills, because they learn to design and test aircraft models to fly stable and long through thermodynamic calculations and other scientific approaches, so that physics education can also be absorbed in an applicative and fun way.